2020
DOI: 10.3390/met10020277
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties, Thermal Stability and Microstructures of W-Re-ZrC Alloys Fabricated by Spark Plasma Sintering

Abstract: Tungsten materials, used as friction stir welding tools, undergo severe plastic deformation and even collapse at high operating temperatures. In order to improve the low-temperature toughness and high-temperature strength, W-10wt.%Re-0.5wt.%ZrC alloys were processed by high-energy ball milling and subsequent spark plasma sintering. Single solid-solution W-Re powders with typical body-centered cubic structures were achieved when the milling time increases to 50 h. The microhardness, tensile properties, thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…That high thermal stress could cause tearing along grain boundaries, which are embrittled by the oxidation and resulting impurities [ 4 , 9 , 22 , 23 ]. It has been reported that a high concentration of oxygen and impurities segregate to the grain boundaries during the cooling process of melted tungsten in SLM [ 9 , 24 ], and the strength of pure tungsten and tungsten alloys are greatly affected by the oxides distributed at grain boundaries [ 22 , 25 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…That high thermal stress could cause tearing along grain boundaries, which are embrittled by the oxidation and resulting impurities [ 4 , 9 , 22 , 23 ]. It has been reported that a high concentration of oxygen and impurities segregate to the grain boundaries during the cooling process of melted tungsten in SLM [ 9 , 24 ], and the strength of pure tungsten and tungsten alloys are greatly affected by the oxides distributed at grain boundaries [ 22 , 25 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the average coefficient of friction (COF) and wear rate of the W-25Re significantly decreased after adding the HfC, effectively improving the tribological performance of the W-25Re [ 95 ]. Though the HfC improved the high-temperature strength of the W-25Re, it also reduced the toughness of the W-25Re, ultimately leading to intergranular fracturing and wear failure [ 96 ].…”
Section: Properties and Strengthening Methods Of W-re Alloymentioning
confidence: 99%
“…It was found that the recrystallization temperature of the W-1Re-0.5ZrC was about 1600–1700 °C, which was significantly higher than that of pure W (1200 °C) [ 37 ]. Miao et al observed that the microstructure and hardness of W-10Re-0.5ZrC changed little after annealing at 1500 °C for 1 h. The tensile strength and elongation behavior of W-10Re-0.5ZrC at 300 °C were 818 MPa and 8.1%, respectively [ 96 ]. Recently, Miao et al studied the effects of ZrC on the properties of W-25Re-0.3ZrC.…”
Section: Properties and Strengthening Methods Of W-re Alloymentioning
confidence: 99%
“…That high thermal stress could cause tearing along grain boundaries, which are embrittled by the oxidation and resulting impurities 4,9,18,19 . It has been reported that a high concentration of oxygen and impurities segregate to the grain boundaries during the cooling process of melted tungsten in SLM 9,20 , and the strength of pure tungsten and tungsten alloys are greatly affected by the oxides distributed at grain boundaries 18,[21][22][23][24] .…”
Section: Metallurgical Defectsmentioning
confidence: 99%